2021
DOI: 10.1080/15332667.2021.1933870
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model of Social Media Brand Love: Mediators of Brand Attitude and Consumer Satisfaction

Abstract: Hawliau Cyffredinol / General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 111 publications
0
5
0
3
Order By: Relevance
“…Thus, consumers who recognize a positive brand image tend to believe that the brand succeeds in offering high satisfaction (Mohammed and Rashid 2018;Zehra and Arshad 2019). Additionally, in the context of social media, it can be concluded that a favorable brand image increases consumer satisfaction (Arghashi et al 2021). Thus, the following hypothesis arises: H4.…”
Section: H3 Csr Initiatives Positively Impact Customer Satisfactionmentioning
confidence: 99%
“…Thus, consumers who recognize a positive brand image tend to believe that the brand succeeds in offering high satisfaction (Mohammed and Rashid 2018;Zehra and Arshad 2019). Additionally, in the context of social media, it can be concluded that a favorable brand image increases consumer satisfaction (Arghashi et al 2021). Thus, the following hypothesis arises: H4.…”
Section: H3 Csr Initiatives Positively Impact Customer Satisfactionmentioning
confidence: 99%
“…Menurut banyak penelitian, mempertahankan konsumen yang sudah ada membutuhkan biaya lima kali lipat daripada mendapatkan konsumen baru (Arghashi et al, 2021). Kepuasan pelanggan adalah gagasan bahwa klien puas dengan cara menjalankan bisnis itu sendiri dan menawarkan barang dan jasa (Chaerudin & Syafarudin, 2021).…”
Section: Kepuasan Konsumenunclassified
“…Pemasaran media sosial didefinisikan sebagai suatu proses yang dilakukan oleh perusahaan dalam berkomunikasi dan melakukan kegiatan pemasaran online melalui media sosial platform media untuk membangun dan memelihara hubungan pemangku kepentingan dengan berinteraksi, berbagi informasi, dan merekomendasikan pembelian. Menurut Arghashi et al, (2021) dan Barreda et al, (2015) ada empat dimensi pemasaran media sosial, yaitu: interaktivitas, personalisasi, keinformatifan, dan word-of-mouth (WOM).…”
Section: Social Media Marketingunclassified